Factors to be considered in the design of indigenous communities' houses, with a focus on Australian first nation housing in the Northern Territory - Ali Rajabipour; Cat Kutay; John Guenther; Milad Bazli (Development Engineering, 2023)
Housing in remote Australia's Indigenous communities has remained an unsolved challenge after many years of effort. Factors to be considered in remote housing have been researched broadly but rarely taking a holistic design point of view. This requires the inclusion of all factors that affect the success of a design project (eg resources, physical and social environment and processes). This study is a response to the question: which factors should engineers consider in their remote Indigenous communities building projects? In this study, these factors were extracted from a literature review. Special emphasis was put on resources related to the Northern Territory remote housing. Ten key factors which thus form goals for the establishment of any project were found after filtering and organising the findings from different publications. Experts in remote housing from the government, private sector and academia were then interviewed to gather their opinion on the solutions with respect to each factor. The results of this study will provide designers with a practical to-do list for planning and implementing their projects in remote communities. Further, the results could be used by decision-makers in developing policies.
Keywords: 330; Remote housing; Community housing; Remote construction